2013
DOI: 10.5090/kjtcs.2013.46.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a Totally Implantable Central Venous Port System with Percutaneous Subclavian Vein Access

Abstract: BackgroundThe role of totally implantable central venous port (TICVP) system is increasing. Implantation performed by radiologist with ultrasound-guided access of vein and fluoroscope-guided positioning of catheter is widely accepted nowadays. In this article, we summarized our experience of TICVP system by surgeon and present the success and complication rate of this surgical method.Materials and MethodsBetween March 2009 and December 2010, 245 ports were implanted in 242 patients by surgeon. These procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
2
18
0
1
Order By: Relevance
“…Similar to our study, Keum et al analyzing only patients undergoing TIVAD implant through SCB found no intraoperative complications as well [2].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, Keum et al analyzing only patients undergoing TIVAD implant through SCB found no intraoperative complications as well [2].…”
Section: Discussionsupporting
confidence: 92%
“…According to the large case series, the rate of catheter mispositioning following TIVAP insertion varies between 0.2% and 3.1% [2,[7][8][9][10][11][12][13][14][15][16][17] (Table 1). [16] 2018 3000 0.2% 9.6% Kim et al [17] 2019 843 0.3% 4%…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that TIVAP insertion under imaging guidance reduces the procedure-related complication rates [18][19][20]. On the other hand, surgeons use either cut-down or percutaneous landmark-based technique for implantation, with low complication rates [2,[7][8][9][10][11][12][13][14][15][16][17]. Since we, the surgeons, are very familiar with blind-landmark technique as well as vascular anatomy of neck and chest regions, and also may recognize and treat the potential procedure-related complications quickly and properly, we applied the blindlandmark technique during TIVAP insertion but unfortunately observed this adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Keum et al reported a series with 242 patients who had 245 ports inserted via subclavian vein [10]. All ports were placed by a thoracic surgeon and no radiologic guidance was used.…”
Section: Discussionmentioning
confidence: 99%